020 Proformas: how to ensure compliance and is there any point? The Birmingham experience. (14th September 2011) - Wimalasena, Y; Ahee, P; Borowska, A
Abstract : Objectives and Backgrounds: In most Emergency Departments (EDs) around the country proformas are in use for the management of patients with specific complaints. Proformas improve documentation, handover and are seen to reduce clinical risk by giving visible guidance to physicians. SWBH encompasses two large EDs seeing over 190 000 patients per year. Head injury, alcohol intoxication and headache proformas were introduced in November 2009, following an analysis of serious untoward incidents (SUIs), to decrease these incidents and improve patient safety. This retrospective analysis was done to evaluate if weekly auditing of proforma use and feedback to clinicians would improve compliance of proforma use and to analyse if use of proformas decreased serious untoward incidents. Methods: Each week (from 31 January 2011 to 09 May 2011) the ED records identified as belonging to patients with head injury, alcohol intoxication or headache were identified by manually combing the triage notes. The use of the proformas for these three conditions was audited. Results were emailed weekly to all clinicians and some were contacted individually. Incidents involving these three conditions were retrospectively looked at for the past 3 years (April 2008 to March 2011). Results: During the study period 780 patients with head injuries, 303 with headache and 127 intoxicated patients were seen. Proforma compliance increased from week 1 to week 15 for head injury (36% to 79%), headache (8% to 64%) and intoxication (38% to 62%). The total number of red and amber incidents involving head injury, headache and intoxication rose from 30 in 2008/2009 to 38 in 2009/2010 and decreased to 23 in 2010/2011. Conclusions: Proformas for head injury, alcohol intoxication or headache, were effective at reducing risk and improving patient safety. No patient involved in a serious clinical incident had a proforma used! Our retrospective feedback audit has shown that regular auditing with feedback can improve compliance in proforma use.